UTILIZATION OF STREAMING TECHNOLOGY AS A PUSDAI TV DAKWAH COMMUNICATION MEDIA - Yulia Sariwaty; Diny Fitriawati; Inke Nuari (Jurnal Komunikasi dan Bisnis, 2021)
Advances in information technology provide easy access for religiousinstitutions to communicate and socialize with the wider community. Including facilitating the way for the syiar Islam or better known as Dakwah. One of the contemporary da'wah media that utilizes streaming technology is Pusdai TV. This study aims to analyze the use of streaming technology as a medium and communication strategy for da'wah communication by Pusdai TV. This study uses a qualitative research method with a phenomenological approach. Data collection techniques were carried out by means of observation, interviews, and document analysis. The results showed that the first Pusdai TV da'wah communication strategy included message planning through objectives, media selection, main ideas, and audience analysis. Second, the strategic process of making broadcast programming through the stages of idea research, content creation, evaluation and control. Third, the da'wah communication strategy is carried out through internal and external approaches. With all the strategies that have been implemented, active audience feedback is obtained, spiritual fulfillment of audience needs, and audience loyalty.